FDB - Bandaranaike, Lakshmi Dias. ([Colombo?] : Lakshmi Dias Bandaranaike, 1994)
Contributed articles on Felix Reginald Dias Bandaranaike, 1930-1985, politician from Sri Lanka.
Includes passages in Sinhalese and Tamil.
Keywords: Politicians -- Sri Lanka -- Biography; Sri Lanka -- Politics and government